Impact of two arbuscular mycorrhizal fungi on Arundo donax L. response to salt stress - Pollastri, Susanna; Savvides, Andreas M.; Pesando, Massimo; Lumini, Erica; Volpe, Maria Grazia; Ozudogru, Elif Aylin; Faccio, Antonella; De Cunzo, Fausta; Michelozzi, Marco; Lambardi, Maurizio; Fotopoulos, Vasileios; Loreto, Francesco; et al. (My University, 2018)
Main conclusion: AM symbiosis did not strongly affectArundo donax performances under salt stress, although differences in the plants inoculated with two different fungi were recorded. The mechanisms at the basis of the improved tolerance to abiotic stresses by arbuscular mycorrhizal (AM) fungi have been investigated mainly focusing on food crops. In this work, the potential impact of AM symbiosis on the performance of a bioenergy crop, Arundo donax, under saline conditions was considered. Specifically, we tried to understand whether AM symbiosis helps this fast-growing plant, often widespread in marginal soils, withstand salt. A combined approach, involving eco-physiological, morphometric and biochemical measurements, was used and the effects of two different AM fungal species (Funneliformis mosseae and Rhizophagus irregularis) were compared. Results indicate that potted A. donax plants do not suffer permanent damage induced by salt stress, but photosynthesis and growth are considerably reduced. Since A. donax is a high-yield biomass crop, reduction of biomass might be a serious agronomical problem in saline conditions. At least under the presently experienced growth conditions, and plant–AM combinations, the negative effect of salt on plant performance was not rescued by AM fungal colonization. However, some changes in plant metabolisms were observed following AM-inoculation, including a significant increase in proline accumulation and a trend toward higher isoprene emission and higher H2O2, especially in plants colonized by R. irregularis. This suggests that AM fungal symbiosis influences plant metabolism, and plant–AM fungus combination is an important factor for improving plant performance and productivity, in presence or absence of stress conditions.
Keywords: AM symbiosis; Bioenergy crop; Climate change; Giant reed; Plant tolerance; Salinity